Afatinib in EGFR TKI-naïve patients with locally advanced or metastatic EGFR mutation-positive non-small cell lung cancer: Interim analysis of a Phase 3b study. (February 2021) - de Marinis, Filippo; Laktionov, Konstantin K.; Poltoratskiy, Artem; Egorova, Inna; Hochmair, Maximilian; Passaro, Antonio; Migliorino, Maria Rita; Metro, Giulio; Gottfried, Maya; Tsoi, Daphne; Ostoros, Gyula; Rizzato, Simona; et al.
Highlights: Interim data from a Phase 3b trial investigating afatinib in a real-world setting. TKI-naïve patients with EGFR m + NSCLC received afatinib 40 mg orally, once-daily. Included patients aged ≥65 years, with comorbidities, poor ECOG PS and/or brain mets. Overall, 99.8 % patients had an AE; grade ≥ 3 AEs were reported in 65.8 % patients. This real-world study supports findings from RCTs of afatinib in EGFR m + NSCLC. Abstract: Objectives: Randomized controlled trials have demonstrated that afatinib is a suitable treatment option for patients with epidermal growth factor receptor mutation-positive ( EGFR m +) non-small cell lung cancer (NSCLC). However, such studies often exclude patients treated in routine clinical practice. We report interim results from a Phase 3b, open-label, multicenter, single-arm, exploratory trial, in which afatinib was investigated in a real-world setting. Materials and methods: Patients with EGFR m + tyrosine kinase inhibitor (TKI)-naïve NSCLC received afatinib 40 mg orally, once-daily, until disease progression, or voluntary withdrawal. Primary objective was safety. Results: Overall, 479 patients received afatinib: median age 65 years, 8 % of patients had an ECOG performance status ≥ 2, 17 % had brain metastases, and 13 % had tumors containing uncommon mutations only. All but one patient (99.8 %) had an adverse event (AE). Treatment-related AEs (TRAEs; any/grade ≥ 3) occurred in 97 %/44 % of patients; most common were diarrhea (87 %/16 %) and rash (51 %/11 %). AEs leading to afatinib dose-reduction were reported in 258 patients (54 %), and 37 patients (8 %) discontinued treatment due to a TRAE. Objective response rate was 45.5 %, median duration of response was 14.1 months (95 % CI: 12.2–16.4). Overall median time to symptomatic progression and progression-free survival were 14.9 months (95 % CI: 13.8–17.6) and 13.4 months (95 % CI: 11.8–14.5), respectively, in the overall population and 19.3 months (95 % CI: 15.6–21.8) and 15.9 months (95 % CI: 13.9–19.1) in patients with EGFR exon 19 deletions. Conclusions: Afatinib administration in routine clinical practice was well tolerated with no new safety signals and demonstrated promising efficacy in patients with EGFR m + NSCLC. TRAEs were generally manageable with tolerability-guided dose reductions. Overall, these data independently support findings from randomized controlled trials of afatinib in EGFR m + NSCLC.